Fourier analysis of thick cross-ply Levy type clamped doubly-curved panels - Oktem, Ahmet Sinan; Chaudhuri, Reaz A. (ELSEVIER SCI LTD, 2007)
A hitherto unavailable Levy type analytical solution to the problem of deformation of a finite-dimensional general cross-ply thick doubly-curved panel of rectangular plan-form, modeled using a higher order.shear deformation theory (HSDT), is presented. A solution methodology, based on a boundary-discontinuous generalized double Fourier series approach is used to solve a system of five highly coupled linear partial differential equations, generated by the HSDT-based laminated shell analysis, with the C4-type simply supported boundary condition prescribed on two opposite edges, while the remaining two edges are subjected to the SS3-type constraint. The numerical accuracy of the solution is ascertained by studying the convergence characteristics of the deflection and moment of a cross-ply spherical panel, and also by comparison with the available FSDT (first-order shear deformation theory) based analytical solution. Additionally, numerical results pertaining to flat symmetric and antisymmetric cross-ply plates with the same boundary conditions have also been reproduced. Hitherto unavailable important numerical results presented include sensitivity of the predicted response quantities of interest to shell geometry (cylindrical and spherical), lamination, lamina material property, and thickness effects, as well as their interactions. Comparison with their SS2 counterparts demonstrates the effect of end clamping on the deflections and moments of thin to thick singly- and doubly-curved cross-ply panels. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: thick laminate; higher order shear deformation theory (HSDT); doubly-curved panel; spherical shell; cylindrical shell; cross-ply; analytical solution; boundary discontinuous double Fourier series; boundary constraints; BOUNDARY-VALUE-PROBLEMS; FREQUENCY-RESPONSE; FREE-VIBRATION; SHELL; Mechanics; Materials Science